Optimasi Pengembangan Embung di Indonesia - Notoatmojo, Budiman; Rivai, Rudi (Journal the Winners: Economics, Business, Management, and Information System Journal, 2001)
Article performs the optimationÂ  of embung utilizationÂ  in Indonesia, especially in NTT province. It is a descriptive using farmer as respondents who use embung as source of drinking water, irrigation, drinking water and field irrigation, as well as drinking water and farm irrigation. It is concluded that embung is a source of developing horticulture in the urban areas.